Lipids of chicken epidermis. - P W Wertz; P M Stover; W Abraham; D T Downing (Journal of Lipid Research, 1988)
The lipids from chicken epidermis were analyzed by a combination of quantitative thin-layer and gas-liquid chromatography and by chemical and spectroscopic methods. The lipid groups present included wax diesters (34%), triglycerides (32%), sterols (11%), phospholipids (11%), nonphosphorus-containing sphingolipids (3%), beta-D-glucosylsterols (3%), 6-O-acyl-beta-D-glucosylsterols (2%), steryl esters (1%), cholesteryl sulfate (1%), and free fatty acids (1%). The major phospholipids were phosphatidylcholine, phosphatidylethanolamine, and sphingomyelin, and the sphingolipids included ceramides, glucosylceramides, O-acylceramides, and O-acylglucosylceramides. Glucosylsterols and acylglucosylsterols have not been found in mammalian skin, and may be relevant to the evolutionary history of the epidermal water barrier. The wax diesters contained mainly 16-, 18-, and 20-carbon saturated fatty acids esterified to 20- through 24-carbon threo and erythro 2,3-diols, while the chicken epidermal triglycerides contained some very long-chain (26-40 carbon) saturated fatty acids. These wax diesters and unusual triglycerides may be of significance in human health.